Mathematical model for the prediction of available phosphorus and calcium requirements for European quails of 16-36 days old (Research, Society and Development, 2020)
Were used 724 quails, with initial weight of 105.05±1.40g to determine the model requirements for European quails 16-36 days old. Were used 384 quails for the maintenance requirement experiment and 240 for the gain requirement experiment and the remaining 100 quails composed the birds of the comparative slaughter. Maintenance requirement: the treatments consisted of four levels of feed offerings (100, 75, 50 and 25% of consumption ad libitum) with four pens and four quails per pen for each climatic environment (18, 24 and 28ºC), being 192 quails for each nutrient under study. Gain requirement: the requirements of the studied nutrients for gain were determined from 240 quails, created and fed ad libitum, being 120 quails for each nutrient studied, that is, 30 quails were slaughtered at 21, 26, 31 and 36 days of age. The quails of the reference slaughter comprise the same as the experiment for determining the maintenance requirement. In conclusion. The prediction equations for estimating the requirements were: 1) Pr (mg/quail/day) = (27.029 + 1.5943 × T) × kg0.75 + 12.24 × WG, in which Pr is the phosphorus requirement, kg0.75 is metabolic weight (kg), WG is weight gain (g/quail/day). 2) Ca (mg/quail/day) = (158.93 - 5.187 × T) × kg0.75 + 23.66 × WG, in which Ca is the calcium requirement, kg0.75 is metabolic weight (kg), WG is weight gain (g/quail/day), T is temperature.